Neutrophils and Activated Macrophages Control Mucosal Immunity by Proteolytic Cleavage of Antileukoproteinase - Vandooren, Jennifer; Goeminne, Pieter; Boon, Lise; Ugarte-Berzal, Estefania; Rybakin, Vasily; Proost, Paul; Abu El-Asrar, Ahmed M.; Opdenakker, Ghislain (Frontiers in Immunology, 2018)
Antileukoproteinase or secretory leukocyte peptidase inhibitor is a small protein which protects the mucosal linings against excessive proteolysis, inflammation and microbial infection. We discovered that gelatinase B or matrix metalloproteinase-9, a secreted zinc-dependent endopeptidase typically found at sites of inflammation, destroys antileukoproteinase by cleavages within both of its two functional domains: the anti-microbial N-terminal and the anti-proteolytic C-terminal domains. Cleaved antileukoproteinase possessed a significantly lower ability to bind lipopolysaccharides and a reduced capacity to inhibit neutrophil elastase activity. Whereas intact antileukoproteinase repressed proinflammatory transcript (PTGS2 and IL6) synthesis and protein secretion (e.g. of matrix metalloproteinase-9) in human CD14+ blood monocytes stimulated with lipopolysaccharides, this effect was reduced or lost for cleaved antileukoproteinase. We demonstrated the in vivo presence of antileukoproteinase cleavage fragments in lower airway secretions of non-cystic fibrosis bronchiectasis patients with considerable levels of neutrophils and, hence, elastase and matrix metalloproteinase-9 activity. As a comparison, other matrix metalloproteases (MMP-2, MMP-7 and MMP-8) and serine proteases (neutrophil elastase, cathepsin G and proteinase 3) were also able to cleave antileukoproteinase with similar or reduced efficiency. In conclusion, in specific mucosal pathologies, such as bronchiectasis, neutrophils and macrophage subsets control local immune reactions by proteolytic regulation, here described as the balance between matrix metalloproteases (in particular matrix metalloproteinase-9), serine proteases and local tissue inhibitors.